The Effectiveness of Audiovisual Media Education on Mothers' Knowledge Regarding the Prevention of Postpartum Infections - Retno Sri Wulandari; Susanti Pratamaningtyas; Sumy; ⁠Ririn Indrian (Gayaku Publisher, 2026)
Background: Postpartum infection remains one of the leading causes of maternal morbidity and mortality. Limited maternal knowledge regarding infection prevention contributes to postpartum complications. Audio-visual education is considered an effective learning strategy because it simultaneously stimulates visual and auditory senses. Objective: To determine the effectiveness of audio-visual education on mothers' knowledge regarding postpartum infection prevention at Kediri District Hospital. Methods: A pre-experimental study using a One Group Pre-test Post-test design was conducted among 34 postpartum mothers. Knowledge was measured using questionnaires before and after the intervention. Data were analyzed using the Wilcoxon Match Pairs Test with a significance level of 0.05. Results: Prior to the intervention, most respondents demonstrated moderate knowledge. Following audio-visual education, most respondents achieved good knowledge. Statistical analysis showed a significant improvement after the intervention (p=0.000). Audio-visual media enhanced mothers' understanding through integrated visual and auditory stimulation, improving learning retention and facilitating better comprehension of postpartum infection prevention. Conclusion: Audio-visual education significantly improves mothers' knowledge regarding postpartum infection prevention and can be implemented as an effective health education strategy in midwifery services.